Moderasi Beragama Berbasis Budaya dan Kearifan Lokal Masyarakat NU dan Muhammadiyah di Kampung Kejawan Pesisir Suramadu Bangkalan Madura - Musya'adah, Umi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This article explains religious moderation based on culture and local wisdom of the NU and Muhammadiyah communities on the Suramadu coast, Kejawan Village, Bangkalan, Madura. This article describes a portrait of local culture and wisdom that can strengthen the religious moderation of the coastal communities of Suramadu, Bangkalan Madura, there are several areas on the coast of Suramadu where the daily language is Javanese, or what is usually called Madurese Kejawan (Madureans who speak Javanese). Madurese Kejawan are native Madurese and not descendants of Javanese. This folklore, which is believed to have been passed down from generation to generation in the Madura Kejawan village, is the legacy of the Majapahit soldiers who lost the war and fled to Madura. Meanwhile, in the Kejawan village area, the community is based on NU and Muhammadiyah, according to the author's initial observations, they are harmonious and respect each other and appreciate differences. This portrait of moderation by NU and Muhammadiyah citizens must always be maintained for the next generations. The culture and local wisdom of the Madurese people who like to consider fellow Madurese as their own brothers